2011
DOI: 10.1007/s12070-010-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Trial to Verify the Efficacy of Pre-Operative Intra Venous Tranexamic Acid in the Control of Tonsillectomy Bleeding

Abstract: Tonsillectomy is an age old surgery which is still very commonly done. Bleeding related to surgery is the major problem. This study is done to verify by randomized control trial the efficacy of preoperative intravenous tranexamic acid in the control of tonsillectomy bleeding. Hundred cases undergoing tonsillectomy were randomized into two groups, one of which received preoperatively intra venous tranexamic acid, 10 mg kg -1. The other group patients were given a placebo. Amount of bleeding was assessed in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
2
26
0
1
Order By: Relevance
“…Against our result, there are two studies showed that the preoperative intravenous tranexamic acid is effective and significantly decreased the tonsillectomy bleeding [18,19]. In a randomized controlled trial, a single dose of intravenous perioperative tranexamic acid at l0 mg/kg produced a mean blood loss of 56.61 ml compared with 66.52 ml in the control group during tonsillectomy using conventional dissection techniques [20].…”
Section: Discussionmentioning
confidence: 68%
“…Against our result, there are two studies showed that the preoperative intravenous tranexamic acid is effective and significantly decreased the tonsillectomy bleeding [18,19]. In a randomized controlled trial, a single dose of intravenous perioperative tranexamic acid at l0 mg/kg produced a mean blood loss of 56.61 ml compared with 66.52 ml in the control group during tonsillectomy using conventional dissection techniques [20].…”
Section: Discussionmentioning
confidence: 68%
“…Thus, intraoperative bleeding was less in group-A Patients who has received tranexamic acid injection intra-operatively as compare to group-B patients which has received the same amount of normal saline. (29). No side effect of the tranexamic acid was mentioned in studies.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to surgery, tranexamic acid was also used with great success to reduce bleeding in non-operative certain situations, including epistaxis, topmost GIT bleeding, and menorrhagia, that also showed significant decrease in bleeding through the use of tranexamic acid. In spite of the enormous evidence in support of tranexamic acid success in preventing bleeding throughout tonsillectomy, studies have been conducted in which tranexamic acid has not proved to be useful, this could be due to tranexamic acid which may not have an effect on blood vessels bleeding and is more successful in managing capillary oozing (29). That's why in certain patients who underwent, in spite of giving tranexamic acid intraoperative intravenous injection does not reduce intraoperative bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed no significant benefit from the routine use of tranexamic acid during tonsillectomy, 30 while others have confirmed a significant reduction in blood loss during surgery using conventional dissection techniques. 33 The authors reported no adverse effects from tranexamic acid. 33 The authors reported no adverse effects from tranexamic acid.…”
Section: Tonsillectomymentioning
confidence: 88%
“…One study showed no significant benefit from the routine use of tranexamic acid during tonsillectomy, 30 while others have confirmed a significant reduction in blood loss during surgery using conventional dissection techniques 31 , 32 . In a further randomised, controlled trial, a single dose of intravenous, peri-operative tranexamic acid at 10 mg/kg was associated with a mean blood loss of 36.64 ml, compared with 66.32 ml in the control group 33 . The authors reported no adverse effects from tranexamic acid.…”
Section: Tonsillectomymentioning
confidence: 89%